Prezi-Based Learning Media Improves Understanding of Content and Messages from Fairy Tales for Third Grade Elementary School Students - Tantri Widyastuti; Sukarir Nuryanto (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Problems often occur in the field because learning media are unavailable or must meet curriculum needs. This has an impact on students' abilities and understanding, which need to be improved. Based on this, this study aims to develop Prezi-based learning media to improve understanding of the content and messages of fairy tales for grade III Elementary School students. This research method is the Research and Development research method using the Research Procedure according to Borg & Gall. Expert validators are media experts and material experts. Teachers and students carry out practical tests. Small-scale product trials using 8 grade III students and large group trials using 23 students. Data collection methods include observation, interviews, questionnaires, documentation, and tests. The research instrument is a questionnaire. The data analysis techniques used are qualitative, quantitative, descriptive analysis, and inferential statistics. The study showed that material experts' results at the product validation stage obtained a score of 90.9%, and media experts obtained a score of 85.4%, which was included in the very feasible category. The effectiveness of the media was tested by calculating the initial and final test scores using a paired t-test to obtain differences in student abilities and learning outcomes before and after implementing Prezi-based learning media. It is concluded that Prezi-based learning media can improve students' abilities to understand fairy tale material and can convey fairy tale messages in Indonesian language learning content.